A public opinion survey of four future scenarios for Australia in 2050. (March 2019) - Chambers, Ian; Costanza, Robert; Zingus, Logan; Cork, Steve; Hernandez, Marcello; Sofiullah, Ahmad; Htwe, Thet Z.; Kenny, Danny; Atkins, Paul; Kasser, Tim; Kubiszewski, Ida; Liao, Yilei; et al.
Highlights: In 2016 a national survey (representative and self select samples) was conducted to determine future scenario preferences for Australia in 2050. Four plausible scenarios options were presented: Free Enterprise, Strong Individualism, Community Well-Being, Coordinated Action. Survey results showed a preference for the Community Well-being (CW) scenario: 73% (representative) and 61% (self select) ranked CW as 1 st or 2 nd . However participants ranked Free Enterprise 1 st when asked where Australia is now and is heading: 32% (representative) and 50% (self select). This dissonance between the future Australians want and where they perceive Australia is headed has clear policy implications which we discuss. Abstract: Scenario planning and the use of alternative futures have been used successfully to assist organisations, communities and countries to move towards desired outcomes (Dator, 2009 ). In this study we used a unique combination of scenario planning and a national public opinion survey to explore preferred futures for Australia in 2050. The approach used four future scenarios for Australia in 2050 as the basis for an online national public opinion survey entitled Australia: Our Future, Your Voice. Scenario development was based on a review of a broad range of scenarios for Australia and globally. We then developed four synthesis scenarios based on two axes of individual versus community orientation, and national focus on GDP growth versus a focus on well-being more broadly defined. The scenarios were labelled: (1) Free Enterprise (FE); (2) Strong Individualism (SI); (3) Coordinated Action (CA); and (4) Community Well-being (CW). We created a website that described each of these scenarios and invited people to complete a survey after they had reviewed the scenarios. The survey engaged 2575 adults in two groups: (1) a targeted statistically representative national sample (n = 2083) and (2) a self-selected sample (n = 492). Results from both groups and across all demographic categories revealed that a majority of participants preferred the Community Well-being (CW) scenario. 73% (Representative) and 61% (Self Select) ranked this scenario as 1 st or 2 nd . We also asked which scenario Australia was headed toward. 32% of the Representative sample and 50% of the Self-Selected sample participants ranked the Free Enterprise (FE) scenario as the most likely future. CW was ranked least likely to be 'where Australia is heading?' The dissonance between the future Australians want and where they thought the country is headed has clear policy implications, which we discuss. This extension of scenario planning to include public opinion surveys is novel and this approach can be used to improve thinking, discussion, planning and policy about the future of Australia, as well as potentially other countries and regions.